Borovo gostüvanje v Predanovcih - Ravnik, Mojca (ZRC SAZU, Založba ZRC, 2009)
Borovo gostüvanje, a wedding with a pine tree, is a Carnival tradition characteristic of the region of Prekmurje in northeast Slovenia~of the Porabje in Hungary and the area extending toward northeast Hungaria~and of Austrian Burgenland and Styria. The custom was traditionally held if there had not been a single wedding in the village during fášenk time (the period between Christmas and Shrovetide). In the present time, this is no longer relevant. The tradition is recreated in order to collect funds for village matters, particularly for the local fire brigade~to keep the tradition going~and to attract tourists. Elderly villagers say that the principal objective has always been to do something for the village and its development.This text focuses on the village of Predanovci, where the custom had been observed by this author in 2002. Yet the author did not limit herself merely to this event but analyzed previous ones as well~examined the ways in which the older generation of the villagers still remembered the custom from their younger days~their relation to village traditions~and their perspective on the importance of this custom in the past and at present.